2019
DOI: 10.24815/siele.v6i2.14784
|View full text |Cite
|
Sign up to set email alerts
|

EFL students’ ability in writing reviews for a novel at a university in Medan

Abstract: This research aimed at investigating the ability of the fourth semester English Education Department students at the University of Potensi Utama, Medan, in writing a review text of a novel entitled ‘Sengsara Membawa Nikmat’ written by Toelis Soetan Sati. This study applied a qualitative approach through writing tests as the data collection instrument. The data were, furthermore, analyzed by identifying and evaluating the students’ writing test. The result reveals that overall, the students’ review texts on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…In writing review text, the students admitted that they should think critically due to produce an objective review, not from their subjective view. This statement align with Uswar and Andriani (2019) that review text had to be related to products that happen in real world, it was not just narratives with the theme of common imagination.…”
Section: Critical Thinking On Students' Review Textsupporting
confidence: 61%
“…In writing review text, the students admitted that they should think critically due to produce an objective review, not from their subjective view. This statement align with Uswar and Andriani (2019) that review text had to be related to products that happen in real world, it was not just narratives with the theme of common imagination.…”
Section: Critical Thinking On Students' Review Textsupporting
confidence: 61%
“…The genre tackled in this study is the review text. A review is "an evaluation of a publication, product, service, or company" (Uswar & Andriani, 2019). Likewise, Gerot and Wignell (1995) define a review as "a text that serves to weigh, assess, and submit a criticism of the work or events".…”
Section: The Review Text As a Genrementioning
confidence: 99%
“…Thus, many EFL research have reported the writing difficulties faced by the students. For example, the EFL students cannot clearly express ideas (i.e., Faraj, 2015;Ibnian, 2017: Jayanti, 2019Alagozlu, 2007); they cannot organize the sentences cohesively and coherently (i.e., Chanyoo, 2018;Iseni, Almasaeid, & Younes, 2016); they do not have sufficient knowledge to use the mechanics (i.e., Sajedi, 2014;Uswar & Andriani, 2019;Ghufron & Roshida, 2018;Ibnian, 2017); they do not have sufficient knowledge to apply correct grammar forms (i.e., Yusuf, Mustafa, & Iqbal, 2021;Mohammad & Hazarika, 2016;Ariyanti, 2016;Rezaei & Jafari, 2014); and they do not have sufficient knowledge of vocabulary (Viera, 2017;Faraj, 2015;Ahmed, 2019;Sermsook, Liamnimit, & Pochakorn, 2017;Shokrpour, & Fallahzadeh, 2007). In addition, the EFL students may have received some knowledge from their teachers how to write the text but they they do not know how implement them to produce a proper text Farooq & Wahid, 2018;Bennui, 2016).…”
Section: Introductionmentioning
confidence: 99%